2020
DOI: 10.1108/ijrdm-03-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

The influence of showrooming on Millennial generational cohorts online shopping behaviour

Abstract: PurposeOmnichannel retailing has changed the behaviour of consumers by empowering activities like showrooming which is the process of collecting product information in store then making the purchase online. Since individuals, particularly Millennials, interact with multiple touchpoints throughout their shopping journey, retailers must consider how these experiences influence purchasing behaviour. Literature regarding showrooming has focussed primarily on antecedents to the phenomenon and the negative effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 77 publications
(101 reference statements)
1
42
0
Order By: Relevance
“…For example, Poncin and Mimoun (2014) investigated how to integrate new technologies into brick-and-mortar stores and the impact on positive affective reactions. Bell et al (2017) found IJRDM 50,7 that showrooms in omni-channel retailing can attract customers and generate spillover effects to the other channels, like increasing online shopping intention related to product and financial risk (Johnson and Ramirez, 2020). Through mitigating consumer fit uncertainty, physical showrooms provide shoppers with a complete and satisfactory experience (Li et al, 2020).…”
Section: Literature Review 21 Integrated Store In Omni-channel Retailingmentioning
confidence: 99%
“…For example, Poncin and Mimoun (2014) investigated how to integrate new technologies into brick-and-mortar stores and the impact on positive affective reactions. Bell et al (2017) found IJRDM 50,7 that showrooms in omni-channel retailing can attract customers and generate spillover effects to the other channels, like increasing online shopping intention related to product and financial risk (Johnson and Ramirez, 2020). Through mitigating consumer fit uncertainty, physical showrooms provide shoppers with a complete and satisfactory experience (Li et al, 2020).…”
Section: Literature Review 21 Integrated Store In Omni-channel Retailingmentioning
confidence: 99%
“…Retailers embrace these channels exploring the idea of an omnichannel as a competitive requirement (Brynjolfsson et al, 2013) that blends offline and online shopping into a broader, more reliable, consistent experience to customers (Verhoef et al, 2015). Our view of the research in operations management (Bell et al, 2014;Gallino and Moreno, 2014;Gao and Su, 2017;Akturk et al, 2018) and consumer behaviour (Berman and Thelen, 2018;Shen et al, 2018;Du et al, 2019;Johnson and Ramirez, 2020;Maggioni et al, 2020) advance the understanding of new practices in the omnichannel such as ship-to-store (STS) and buy-Moderating effect of brickand-mortar store 1259…”
Section: Introductionmentioning
confidence: 99%
“…Online shopping is redefining business operations and transforming consumers’ purchasing experience (Daroch et al , 2021; Johnson and Ramirez, 2020). Consumers can buy anything online with a click from online retailers.…”
Section: Introductionmentioning
confidence: 99%